The influence of age, sex, and exercise on autophagy, mitophagy, and lysosome biogenesis in skeletal muscle - Matthew Triolo; Ashley N. Oliveira; Rita Kumari; David A. Hood (Skeletal Muscle, 2022)
Abstract Background Aging decreases skeletal muscle mass and quality. Maintenance of healthy muscle is regulated by a balance between protein and organellar synthesis and their degradation. The autophagy-lysosome system is responsible for the selective degradation of protein aggregates and organelles, such as mitochondria (i.e., mitophagy). Little data exist on the independent and combined influence of age, biological sex, and exercise on the autophagy system and lysosome biogenesis. The purpose of this study was to characterize sex differences in autophagy and lysosome biogenesis in young and aged muscle and to determine if acute exercise influences these processes. Methods Young (4–6 months) and aged (22–24 months) male and female mice were assigned to a sedentary or an acute exercise group. Mitochondrial content, the autophagy-lysosome system, and mitophagy were measured via protein analysis. A TFEB-promoter-construct was utilized to examine Tfeb transcription, and nuclear-cytosolic fractions allowed us to examine TFEB localization in sedentary and exercised muscle with age and sex. Results Our results indicate that female mice, both young and old, had more mitochondrial protein than age-matched males. However, mitochondria in the muscle of females had a reduced respiratory capacity. Mitochondrial content was only reduced with age in the male cohort. Young female mice had a greater abundance of autophagy, mitophagy, and lysosome proteins than young males; however, increases were evident with age irrespective of sex. Young sedentary female mice had indices of greater autophagosomal turnover than male counterparts. Exhaustive exercise was able to stimulate autophagic clearance solely in young male mice. Similarly, nuclear TFEB protein was enhanced to a greater extent in young male, compared to young female mice following exercise, but no changes were observed in aged mice. Finally, TFEB-promoter activity was upregulated following exercise in both young and aged muscle. Conclusions The present study demonstrates that biological sex influences mitochondrial homeostasis, the autophagy-lysosome system, and mitophagy in skeletal muscle with age. Furthermore, our data suggest that young male mice have a more profound ability to activate these processes with exercise than in the other groups. Ultimately, this may contribute to a greater remodeling of muscle in response to exercise training in males.